PEMODELAN INTERAKSI DINAMIKA BIDANG KENDALI DAN PESAWAT UDARA - Wianti, Hasna
Control surfaces on an aircraft play such an important role as its function for controlling aircraft motion. Any failure in control surfaces in floating condition would result influence in motion of the aircraft. Therefore, it is required to study impact of failures in control surfaces partially under floating condition in regards of aircraft motion. Mathematical derivation on equation of motion for floating control surface on aircraft is complex, it would require such an enormous efforts and time. With recent develoment in the field of computing, there is application available for this puprose, Simscape. The application has feature building physical model of control surface system to enable simulation of control surfaces interaction on an aircraft. Simulation would be performed by physically modelling control surfaces within Simscape MATLAB and Simulink MATLAB for the aircraft. Combining both modelling using block feature available within MATLAB software would provide analysis on impact of control surfaces movement on the aircraft. Simulation would also including hinge moment model, providing disruption in the form of step deflection of control surface, and floating type control surface failure. Movement of control surfaces due to oscilation caused by hinge moment, and step deflection disruption, would result to affecting motion of the aircraft. In case of control surface disruption for single floating control surface would cause the aircraft to become unstable , decreasing pitch angle and increasing speed drastically.